West Nile Viral Meningoencephalitis in an Immunocompetent Female: A Case Report from Western Rajasthan, India - Abhishek, Kumar S; Tiwari, Sarika; Kumar, Prawin; Nag, Vijaya L.; Pamnani, Jaya; Tiwari, Sarbesh (Infectious Disorders - Drug Targets, 2021)
Background: West Nile virus (WNV) is a positive-sense single-stranded RNA virus of the family Flaviviridae and genus Flavivirus. The virus is transmitted primarily by the bite of Culex species mosquito and is of global concern. The infection is associated with a wide spectrum of signs and symptoms and is more fatal in the elderly, infants, and immunocompromised individuals. Case Presentation: We report a case of WNV meningoencephalitis in an immunocompetent female who presented with features of acute meningitis with a 5-days history. After the radiological suspicion of viral meningoencephalitis, viral serology was performed and was reactive for IgM antibody against WNV, delaying the diagnosis for at least 5 days. Conclusion: The purpose of this case report is to prime the treating physicians on the usefulness of viral serology in such a scenario. Viral serology is a simple and relatively rapid technique to diagnose or rule out the suspected viral cause of meningoencephalitis and minimize the time gap between diagnosis and start of supporting treatment wherever appropriate antivirals are not available for clinical use.
Keywords: West Nile virus